Processing Shredded Catfish for Community Economic Empowerment in the Meruya Area of West Jakarta - HIDAYAH, Nurul; ASIH, Daru; ANDARI, Putri (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2024)
This community service program aims to empower the economy of Meruya Selatan Village, West Jakarta residents through training in processing catfish into shredded fish. This activity is designed to address the problem of low income and need for food processing skills among local PKK mothers. Through a series of training and mentoring, this program will equip participants with skills in producing quality shredded catfish, preservation techniques, packaging, and effective marketing strategies. Implementation methods include an initial survey, intensive training, hands-on practice, and ongoing monitoring. Other targets include improving participants' knowledge and skills, as well as expanding the marketing reach of shredded catfish products. By utilising local potential and appropriate technology, this programme is expected to increase family income, strengthen food security, and encourage local economic growth in Meruya Selatan Village. PKM activities will end with a discussion session, questions and answers and filling out questionnaires. The output of PKM activities will be published in the form of mass media, articles, and journal publications.